THE ANALYSIS OF PRONUNCIATION ERROR IN PRODUCING VOICED AND VOICELESS CONSONANTS (DESCRIPTIVE STUDY OF TENTH GRADE STUDENTS AT SMAN 1 CILEGON) - Najwan Abdus Salam; Ika Handayani; Rahman Hakim (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2021)
This research used qualitative with a descriptive design. The objectives of this research were to better understand the kinds and patterns of an error made by the tenth-grade students at SMAN 1 Cilegon. The data were collected using a word list, recorder, spectrogram, and scripts. Finally, based on the result of the analysis, it is found that there are three kinds of errors that occurred in producing consonants (/ ʤ / and / ʧ /). The first one is misformation with 67%, the second one is blended with 24% and the last is omission with 9%. For the patterns of error shown that coda is the most a pattern of error that occurred in producing consonants (/ ʤ / and / ʧ /) with a score of 56%, next is onset with a score of 23% and last is medial with a score 21%.